An Analysis of the Implementation of the Job Costing Method in Pricing Determination at PT Banana Cake - Nababan, Daniel Reinhard; Situmorang, Elsaría; Zelmiyanti, Riri (Journal Research of Social Science, Economics, and Management, 2025)
Every business faces challenges and fluctuations that affect its performance and profits. Therefore, careful planning is needed to assist management in estimating the desired profit level. The application of cost-volume-profit analysis focuses on several factors that influence changes in these profit components. In addition, the company must also set the right product selling price to cover the costs incurred. This study aims to analyze the profitability of PT Banana Cake using the application of cost-volume-profit analysis. The method used is a descriptive method with a field study approach. The data used come from primary and secondary sources. The analysis includes cost classification, calculation of the contribution margin and its ratio, calculation of the break-even point, margin of safety and its ratio, and determination of the selling price using the cost-plus pricing method. The results show that the costs incurred consist of variable costs and fixed costs. The contribution margin obtained was Rp 5,142,267 with a ratio of 15.1%; the break-even point was Rp 49,040,167 or 2,347 units; and the margin of safety was Rp 10,227,849 with a ratio of 69%. Determining the product’s selling price using the cost-plus pricing method resulted in a price of Rp 25,658, rounded down to Rp 25,000. Overall, PT Banana Cake’s managerial performance in managing costs and sales has been good and optimal. Therefore, the company’s management can utilize cost-volume-profit analysis for pricing and future profit planning.